Pengaruh Pemberian Formulasi Pupuk NPK + Pupuk Hayati terhadap Pertumbuhan dan Komponen Hasil Jagung Hibrida Varietas BISI 2 di Lahan Rawa Lebak - Sri Yuniarti; Joko Purnomo (AgroGreen, 2026)
This study aims to determine the effect of NPK fertilizer + organic fertilizer formulation on the growth and yield components of hybrid corn variety BISI 2 in swampy land. To obtain the NPK fertilizer + organic fertilizer formulation that provides the best growth and yield components of hybrid corn variety BISI 2 in swampy land. This study was conducted from February to August 2025 in Banyu Hirang Village, Gambut District, Banjar Regency, South Kalimantan. The experimental design used was a single factor Randomized Block Design (RAK). The factors used were the NPK fertilizer + organic fertilizer (K) formulation with 4 treatment levels, namely k1 = 100% NPK fertilizer, k2 = 75% NPK fertilizer + organic fertilizer, k3 = 50% NPK fertilizer + organic fertilizer, k4 = 25% NPK fertilizer + organic fertilizer. The treatment was repeated 6 times to obtain 24 experimental units. Each experimental unit was filled by 14 plants so that a total of 336 plants were obtained. The results of the study showed that the NPK fertilizer formulation had a significant and very significant effect on the variables of plant height at 3, 4, 6 and 7 WAP, number of leaves at 2, 4, 5 and 6 WAP, stem diameter at 4, 5, 6 and 7 WAP, flower emergence time, cob length, number of seeds per row and the 100% NPK fertilizer formulation produced relatively better growth and yield components compared to other treatments.